Use of Long-Distance Migration Patterns of an Endangered Species to Inform Conservation Planning for the World's Largest Marine Protected Area - HAYS, GRAEME C.; MORTIMER, JEANNE A.; IERODIACONOU, DANIEL; ESTEBAN, NICOLE (Conservation biology, 2014)
Large marine protected areas (MPAs), each hundreds of thousands of square kilometers, have been set up by governments around the world over the last decade as part of efforts to reduce ocean biodiversity declines, yet their efficacy is hotly debated. The Chagos Archipelago MPA (640,000 km2) (Indian Ocean) lies at the heart of this debate. We conducted the first satellite tracking of a migratory species, the green turtle (Chelonia mydas), within the MPA and assessed the species' use of protected versus unprotected areas. We developed an approach to estimate length of residence within the MPA that may have utility across migratory taxa including tuna and sharks. We recorded the longest ever published migration for an adult cheloniid turtle (3979 km). Seven of 8 tracked individuals migrated to distant foraging grounds, often ≥1000 km outside the MPA. One turtle traveled to foraging grounds within the MPA. Thus, networks of small MPAs, developed synergistically with larger MPAs, may increase the amount of time migrating species spend within protected areas. The MPA will protect turtles during the breeding season and will protect some turtles on their foraging grounds within the MPA and others during the first part of their long-distance postbreeding oceanic migrations. International cooperation will be needed to develop the network of small MPAs needed to supplement the Chagos Archipelago MPA. Las áreas marinas protegidas grandes (MPAs, en inglés), con cientos de miles de kilómetros cuadrados cada una, han sido establecidas por gobiernos alrededor del mundo a lo largo de la década pasada como parte de los esfuerzos para reducir las declinaciones de biodiversidad oceánica, sin embargo su efectividad sigue siendo tema de debate. La MPA del archipiélago de Chagos (640,000 km2) (Océano Índico) yace al centro de este debate. Llevamos a cabo el primer rastreo satelital de una especie migratoria, la tortuga verde (Chelonia mydas), dentro de la MPA y evaluamos el uso de la especie de áreas protegidas y áreas no protegidas. Desarrollamos una estrategia para estimar la duración de residencia dentro de la MPA que podría tener utilidad para taxones migratorios, incluyendo atunes y tiburones. Registramos la migración más larga jamás publicada para un quelonio adulto (3979 Km). Siete de 8 individuos rastreados migraron a zonas de alimentación distantes, a menudo ≥ 1000 Km fuera de la MPA. Una de las tortugas viajó a zonas de alimentación dentro de la MPA. Así, las redes de pequeñas MPAs, desarrolladas sinérgicamente con MPAs más grandes puede incrementar la cantidad de tiempo que las especies migratorias pasan dentro de áreas protegidas. La MPA protegerá a las tortugas durante la temporada reproductiva y protegerá a algunas tortugas en sus zonas de alimentación dentro de la MPA y a otras durante la primera parte de sus migraciones pos-reproductivas de larga distancia. Se necesitará cooperación internacional para desarrollar la red de pequeñas MPAs necesarias para complementar la MPA del archipiélago Chagos.